Vitamin D levels of obesity and non-obesity health workers: a cross-sectional study in Dr. Sardjito General Hospital/Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, Yogyakarta - Siti Nur Rohmah; Dwita Dyah Adyarini; Prenali Dwisthi Sattwika; Anastasia Evi Handayaningsih; Hemi Sinorita; Vina Yanti Susanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Obesity is one of the causes of chronic diseases, such as diabetes, hypertension, stroke, cancer, dyslipidemia, and heart disease. It is considered a financial burden on national health insurance since it drains the largest health fund. The study aimed to determine the difference in vitamin D levels in obese and non-obese health workers and analyze the factors that influence it. This was a cross-sectional study of the obese and non-obese health workers at Dr. Sardjito General Hospital, Yogyakarta. A total of 50 subjects, including 25 obese and 25 non-obese subjects were involved. Serum vitamin D levels was determined by ELISA. There was no significant difference between the obese and non-obese groups on vitamin D status (p<0.365). Vitamin D deficiency was found in 10% of subjects, whereas insufficient vitamin D levels were found in 46 and 44% of subjects, respectively. Vitamin D deficiency was more common in the obese (12%) than non-obese (8%) group. Contrarily, vitamin D insufficiency was more common in the non-obese (56%) than obese (36%) group. The serum vitamin D levels in the obese [30.08 (14.67-101.71) ng/mL] was not significantly different compare to those non-obese [28.54 (14.38-54.41) ng/mL] (p = 0.691). The multivariate analysis significantly showed that outdoor activities <30 min had a 7.061 times greater risk of having vitamin D deficiency/insufficiency compared to outdoor activities >30 min (OR 7.061; 95% CI: 1.064-46.872; p=0.043). In conclusion, there is no significant difference in vitamin D levels between the obese and non-obese groups. Vitamin D deficiency/insufficiency is more common in non-obese subjects than in obese subjects. Outdoor activity <30 min is a risk factor for vitamin D insufficiency/deficiency despite living in a tropical country with abundant sunlight throughout the year.